The monogenean Paradiplozoon ichthyoxanthon behaves like a micropredator on two of its hosts, as indicated by stable isotopes. Issue 1 (22nd January 2019) - Sures, B.; Nachev, M.; Gilbert, B.M.; Dos Santos, Q.M.; Jochmann, M.A.; Köster, D.; Schmidt, T.C.; Avenant-Oldewage, A.
Abstract: The analysis of stable isotopes of carbon and nitrogen has been used as a fingerprint for understanding the trophic interactions of organisms. Most of these studies have been applied to free-living organisms, while parasites have largely been neglected. Studies dealing with parasites so far have assessed the carbon and nitrogen signatures in endoparasites or ectoparasites of different hosts, without showing general trends concerning the nutritional relationships within host–parasite associations. Moreover, in most cases such systems involved a single host and parasite species. The present study is therefore the first to detail the trophic interactions of a freshwater monogenean–host model using δ 13 C and δ 15 N, where a single monogenean species infects two distinctly different hosts. Host fishes, Labeobarbus aeneus and Labeobarbus kimberleyensis from the Vaal Dam, South Africa, were assessed for the monogenean parasite Paradiplozoon ichthyoxanthon, individuals of which were removed from the gills of the hosts. The parasites and host muscle samples were analysed for signatures of δ 13 C and δ 15 N using an elemental analyser connected to an isotope ratio mass spectrometer. Host fish appear to use partly different food sources, with L. aeneus having slightly elevated δ 13 C signatures compared to L. kimberleyensis, and showed only small differences with regard to their nitrogen signatures, suggesting that both species range on the same trophic level. Carbon and nitrogen signatures in P. ichthyoxanthon showed that the parasites mirrored the small differences in dietary carbon sources of the host but, according to δ 15 N signatures, the parasite ranged on a higher trophic level than the hosts. This relationship resembles predator–prey relationships and therefore suggests that P. ichthyoxanthon might act as a micropredator, similar to blood-sucking arthropods such as mites and fleas.